1979
DOI: 10.1002/jcu.1870070211
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound evaluation of hydronephrosis of pregnancy

Abstract: Four hundred ninety-two patients, including 449 pregnant patients, 39 nonpregnant control patients, and 4 patients with pelvic masses, had renal ultrasonography using gray scale technique. Measurements of renal pelvic diameters in the normal pregnant patients revealed an overall incidence of 63 percent renal pelvic dilatation over the nonpregnant controls. Maximum normal renal pelvic diameters were 1.1 cm on the right and 0.9 cm on the left. The maximum normal expected renal pelvic diameter (97.5 percent confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0
1

Year Published

1981
1981
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 8 publications
(8 reference statements)
2
7
0
1
Order By: Relevance
“…We found the overall incidence of hydronephrosis to be consistent with published studies (table 1) [2,3,5,8]. We also found a predominance of right kidney affections (table 2).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…We found the overall incidence of hydronephrosis to be consistent with published studies (table 1) [2,3,5,8]. We also found a predominance of right kidney affections (table 2).…”
Section: Discussionsupporting
confidence: 81%
“…From the present study the calyceal diameter of ap proximately 50 mm, as 27 mm reported by Erickson et al [2], in the right kidney and 22 mm in the left kidney does not always indicate the presence of a pathology. Conse quently, these patients should receive special attention relative to hydronephrosis from the first trimester through early postpartum.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Muller‐Suur and Tyden [40] measured the renal pelvic diameter and recommended renography in symptomatic patients with a renal pelvic diameter of > 17 mm. In contrast, Erickson et al [41] found a maximum pelvic diameter of 27 mm on the right side and 18 mm on the left side during last two trimesters of pregnancy in asymptomatic patients.…”
Section: Diagnostic Evaluationmentioning
confidence: 91%
“…Erickson et al [12], retiennent à partir du deuxième trimestre, 27 mm à droite et 18 mm à gauche. Brandt et Descroches [13] retiennent les mêmes référen-ces pour le deuxième et le troisième trimestres, les limites pathologiques étant de 18 mm à droite et 15 mm à gauche pour le premier trimestre.…”
Section: L'appréciation De La Dilatation Des Voies Urinairesunclassified